Balancing performance of active magnetic regenerators: a comprehensive experimental study of aspect ratio, particle size, and operating conditions. (15th March 2023) - Czernuszewicz, Agata; Griffith, Lucas; Slaughter, Julie; Pecharsky, Vitalij
Abstract: Effective and, at the same time, efficient active magnetic regenerator (AMR) performance requires balanced geometry and operating conditions. Here the influence of regenerator shape, magnetocaloric material size, operating frequency, and utilization on the performance of gadolinium packed-particle bed AMRs is demonstrated experimentally. Various metrics are applied to assess effectiveness and efficiency. Observed temperature spans and cooling powers across a wide range of operating conditions are used to evaluate system performance and estimate exergetic cooling power and exergetic power quotient. A new metric combining exergetic cooling power and pump power provides an estimate of the maximum achievable second law efficiency. Five regenerator geometries with equal volumes and the aspect ratio from 1.0 to 3.8, and four different ranges of Gd spherical particles between 182 and 354 µ m, are investigated. Improvements in system performance are demonstrated by a boost in specific cooling power of gadolinium from 0.85 to 1.16 W g −1 and maximum temperature span from 8.9 to 15.1 K. The optimum exergetic cooling power is observed for 1.37 utilization and 3 Hz operating frequency, exergetic power quotient exhibits a maximum at the same utilization but at 2 Hz frequency, while the highest efficiency is recorded at 1 Hz and utilization of 0.5, demonstrating that multiple performance metrics must be balanced to achieve regenerator design meeting all performance targets.